Optimizing renewable energy harvesting through the design of a sustainable dual-axis solar tracking system / Mohd Arzaimiruddin Ariffin ... [et al.] - Ariffin, Mohd Arzaimiruddin; Zulkohar, Muhammad Ammar; Cik Izzani, Muhammad Irfan Aiman; Mohd Azrul, Muhammad Amir Firdaus; Mohd Sukri, Muhamad Asyraf Syamil (2024)
Malaysia has significant renewable energy potential, which can be maximized using dual-axis solar tracking systems that maintain optimal alignment with the sun, enhancing energy efficiency. The primary challenge, especially in regions like Bukit Besi in Terengganu with abundant sunlight, is ensuring solar panels remain perpendicular to the sun to maximize energy production, a problem traditional static panels fail to address. This project designs an effective dual-axis solar tracker that continuously adjusts panel orientation for maximum sunlight absorption. The methodology includes mechanical engineering design and simulations using SolidWorks and Tinkercad to ensure structural and circuit functionality. The tracker's performance is verified by measuring the angle of sunlight and input voltage. The result is an optimally designed tracker with a complete electric and control system, significantly boosting solar system efficiency by keeping panels perpendicular to the sun's rays. The design concept and control system have been successfully developed, with future plans for fabrication. This innovation offers commercial potential, providing affordable solutions for integrating renewable energy into the expanding solar market.